MENGUKUR KESUKSESAN SISTEM AKUNTANSI INSTANSI BASIS AKRUAL (SAIBA) MENGGUNAKAN MODEL DeLONE & McLEAN - Noviyanti, Noviyanti (Jurnal Tata Kelola & Akuntabilitas Keuangan Negara, 2016)
The aim of this study is to determine the userâs perception of Accrual Basis Institution Accounting System Â (SAIBA) in the ministry/agency in the first year of implementation of accrual-based governmentâs financial statements. Updated D & M IS Success Model is used to assess the success of SAIBA as a mandatory system in Indonesian Government Accounting. Respondents are operators of Institution Accounting System (SAI) in the ministries/agencies, who are joining the Workshop on Preparation and Study of Financial Statements at Pusdiklat Anggaran dan Perbendaharaan Â Bogor in November 2015 Â and selected using purposive sampling method. The Primary data were obtained through questionnaires that were collected from 204 respondents, which were then analyzed using structural equation modeling. This study found that SAIBA can be categorized as a successful information for each dimension of success in the Updated D&M IS Success Model. Respondents assessed the system quality, the information quality and service quality of SAIBA tend to be good. However, respondents indicated the use of SAIBA has no significant effect on user satisfaction, in contrast to the others constructs relationships, the system quality, the information quality and service quality of SAIBA with net benefit and its reciprocal proved to be significant impact.